Kikuchi pattern simulations of backscattered and transmitted electrons. (9th August 2021) - Winkelmann, Aimo; Nolze, Gert; Cios, Grzegorz; Tokarski, Tomasz; Bała, Piotr; Hourahine, Ben; Trager‐Cowan, Carol
Abstract: We discuss a refined simulation approach which treats Kikuchi diffraction patterns in electron backscatter diffraction (EBSD) and transmission Kikuchi diffraction (TKD). The model considers the result of two combined mechanisms: (a) the dynamical diffraction of electrons emitted coherently from point sources in a crystal and (b) diffraction effects on incoherent diffuse intensity distributions. Using suitable parameter settings, the refined simulation model allows to reproduce various thickness‐ and energy‐dependent features which are observed in experimental Kikuchi diffraction patterns. Excess‐deficiency features are treated by the effect of gradients in the incoherent background intensity. Based on the analytical two‐beam approximation to dynamical electron diffraction, a phenomenological model of excess‐deficiency features is derived, which can be used for pattern matching applications. The model allows to approximate the effect of the incident beam geometry as a correction signal for template patterns which can be reprojected from pre‐calculated reference data. As an application, we find that the accuracy of fitted projection centre coordinates in EBSD and TKD can be affected by changes in the order of 10 − 3 – 10 − 2 if excess‐deficiency features are not considered in the theoretical model underlying a best‐fit pattern matching approach. Correspondingly, the absolute accuracy of simulation‐based EBSD strain determination can suffer from biases of a similar order of magnitude if excess‐deficiency effects are neglected in the simulation model.